“I Would Be an Improviser Even If I Were Born on the Moon”: A Reflective Correspondence on Identity, Movement, and Community - McPherson, Dougal Henry J; Sappho, Maria (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
This reflective correspondence on improvisation and sociality was initiated via a shared Google Document in Summer 2023. It juxtaposes entangled ideas and propositions drawn from the doctoral projects of both authors on issues of identity, mobility, and community within and around free improvisational practice. It forms part of a conversation in progress.